Political Islam and agrarian question: Critique of political economy and critical agrarian approaches (Insights from sharecroppers and agricultural laborers in rural Java) - Khalid Syaifullah; Hanindraputri, Eufrasia Kartika; Inaya, Nur’aini; Indah, Putri Dwi Permata (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2025)
This study examines the relationship between capitalism, agrarian transformation, and the development of political Islam in rural Indonesia, focusing on Bulak Village, West Java. It is grounded in debates concerning the relevance of rural areas as the basis for Islamic social movements in the context of global capitalism. The study seeks to answer how agrarian transformation influences class dynamics and the formation of populist Islam-based movements in rural areas. Using a qualitative approach that integrates interviews, observations, and literature reviews, the study reveals that class differentiation driven by agrarian changes—from the Green Revolution era to the dominance of Chinese entrepreneurs in the 1990s—has created significant inequality in access to agrarian means of production. The ulama (Islamic scholars) and haji (pilgrims) classes leveraged these changes to maintain their socio-economic dominance, while sharecroppers and agricultural laborers were the most adversely affected. This situation led to the formation of populist alliances based on religious narratives opposing the capital expansion of